1994
DOI: 10.1007/bf00178244
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the interleukin-1 gene family in mammals

Abstract: The phylogeny of interleukin-1 family genes shows that human interleukin-1 alpha (IL-1 alpha) is more closely related to IL-1 alpha of the bovine than to IL-1 alpha of the mouse, whereas human interleukin-1 beta (IL-1 beta) is more closely related to IL-1 beta of the mouse than to IL-1 beta of the bovine. The IL-1 receptor antagonist (IL-1ra) shows homology to the C-terminal region of both IL-1 alpha and IL-1 beta. In the C-terminal region, the IL-1 alpha genes of human and mouse have diverged more from each o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…It has been estimated that IL-1ra diverged from IL-1 approximately 350 million years ago (Eisenberg et al, 1991), and thus could be absent in fish. It has also been suggested that the common ancestor of IL-1 and the IL-1ra may have undergone alternative splicing to produce the two di#erent molecules (Hughes, 1994). There is as yet no evidence of this in fish.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been estimated that IL-1ra diverged from IL-1 approximately 350 million years ago (Eisenberg et al, 1991), and thus could be absent in fish. It has also been suggested that the common ancestor of IL-1 and the IL-1ra may have undergone alternative splicing to produce the two di#erent molecules (Hughes, 1994). There is as yet no evidence of this in fish.…”
Section: Discussionmentioning
confidence: 97%
“…The IL-1ra has highest amino acid homology (26%) to IL-1 , and this together with homology between the signal peptide of IL-1ra and the first exon of IL-1 (which is not translated) suggests that IL-1ra evolved from a duplicated IL-1 gene that arose some 350 million years ago ( Fig. 1) (Hughes, 1994). Whilst IL-1ra binds to site A of the IL-1R in a similar manner to IL-1 and IL-1 , it makes a quite di#erent contact with domain 3 and does not interact with the proposed 'receptor trigger site' required for signal transduction (Schreuder et al, 1997).…”
Section: The Il-1 Gene Familymentioning
confidence: 93%
“…36,37 Furthermore, estimates of when IL-1 and IL-1 diverged (285 million years ago) Identical (*) and similar (. or :) residues identified by the CLUSTAL programme are indicated.…”
Section: Discussionmentioning
confidence: 97%
“…This indicates that if the mammalian phylogeny used to construct Fig. 9 is correct then the IL-b genes are not orthologous (Hughes, 1994;p. 10).…”
Section: Figmentioning
confidence: 99%
“…The tree has a cost of 14 (4 duplications d 1 -d 4 and 10 losses) and was computed by reconciling the C-terminal region tree for IL-1 (Hughes, 1994;Fig. 2c) with the mammal tree ((((bovine,sheep),pig),human), rabbit,(mouse,rat)).…”
Section: Figmentioning
confidence: 99%